Aptenia cordifolia Baby Sunrose - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS, 2018)
This document provides an overview of the baby sunrose (Aptenia cordifolia), a versatile ground cover or hanging basket plant known for its dark green foliage and bright red flowers. It details the plant’s characteristics, including its growth habit, leaf and flower features, and optimal growing conditions. The baby sunrose thrives in full sun and well-drained soil, making it suitable for coastal landscapes. The document also highlights its uses in landscaping and offers care tips to maintain its health and appearance. Original publication date October 1999.